2021
DOI: 10.30630/jam.v14i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Inflasi Dan Tingkat Suku Sbi Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Food and Beverarge yang Go Public Di Bursa Efek Indonesia

Abstract: The purpose of this research are to determine and analyse the influence of Inflation and SBI rate to Stock Price at Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange.The population used in this research are all Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange. The sampling technique is a census, so the sample size used was the entire population that 10 Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange. Method us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…This condition will hurt stock prices, where stock prices in the capital market will experience a significant decline. The results of the research support research conducted by (Mayasari, 2019), (Renaldi, 2016) and (Alvian et al, 2019), which found that interest rates hurt stock prices.…”
Section: Discussionsupporting
confidence: 80%
“…This condition will hurt stock prices, where stock prices in the capital market will experience a significant decline. The results of the research support research conducted by (Mayasari, 2019), (Renaldi, 2016) and (Alvian et al, 2019), which found that interest rates hurt stock prices.…”
Section: Discussionsupporting
confidence: 80%
“…Hasil ini juga tidak sejalan dengan penelitian yang dilakukan oleh Santika (2019) membuktikan bahwa menunjukan tiap kenaikan atauppun penurunan terdapat dalam harga saham selalu dipengaruhi dalam poin inflasi. Begitupula penelitian yang dilakukan oleh Mayasari (2019), Ningrum,(2021), Aisyah,(2021) yang mengatakan penurunan tingkat Inflasi mengakibatkan terjadinya perubahan harga saham perusahaan. Adapun penelitian selanjutnya yang sejalan dengan hasil penelitian ini oleh Simandalahi,dkk(2022) dan Safitri,(2021) mengatakan Secara uji parsial dapat dilihat bahwasanya inflasi tidak berpengaruh terhadap harga saham.…”
Section: Pembahasan Pengaruh Tingkat Inflasi Terhadap Harga Sahamunclassified
“…Laba perusahaan yang menurun berpengaruh terhadap harga saham perusahaan. Penelitian yang sama juga dilakukan oleh (Mayasari, 2021) yang menytakan inflasi berpengaruh signifikan terhadap harga saham. Dimasa pandemi peningkatan Inflasi berpengaruh signifikan terhadap harga saham diperusahaan farmasi.…”
Section: Pengaruh Inflasi Terhadap Harga Sahamunclassified